Novel mutation in MASP1 gene in three new patient with 3MC syndrome - Basdemirci, M.; Sen, A.; Ceylaner, S. (Springernature, 2019)
[Abstract Not Available]
51st Conference of the European-Society-of-Human-Genetics (ESHG) in conjunction with the European Meeting on Psychosocial Aspects of Genetics (EMPAG) -- JUN 16-19, 2018 -- Milan, ITALY